Deodorizing fiber, fabric and preparation process thereof

By using biomass-based activated carbon to load aminoguanidine salts and adding sodium alginate and/or carboxymethyl chitosan to the fiber, the problem of poor water washing resistance of deodorant fiber and low elimination rate of 2-nonenal is solved. problem, achieving efficient and long-lasting deodorizing and antibacterial effects.

CN119332363AActive Publication Date: 2025-01-21LUOLAI LIFESTYLE TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411607400.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The activated carbon modified products in the existing deodorization fibers have poor washing resistance and are not high in elimination rate of 2-nonenal.

Method used

The biomass base carbon is used as a porous carrier, and the load amino amino salt is used as a stocent agent, and sodium algina and/or/or/or/or or/or/or/or/or/or/or/or/or/or/or/or/or/or secondary chitoses are added as antibacterial agents and adhesives. Smelting fiber.

Benefits of technology

The elimination rate of odor fiber has the elimination rate of stink molecules such as ammonia, acetic acid, and 2-elenenonaldehyde, and enhanced the water-resistant and persistent antibacterial odor of fiber, and the cost is low and simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129971840000111
    Figure BDA0005129971840000111
  • Figure BDA0005129971840000112
    Figure BDA0005129971840000112
  • Figure BDA0005129971840000121
    Figure BDA0005129971840000121
Patent Text Reader

Abstract

The invention belongs to the technical field of functional fibers, and provides a deodorizing fiber, a fabric and a preparation process thereof, the process comprises the following steps: pretreating biomass, mixing the pretreated biomass with an activator, and preparing activated carbon; the preparation method comprises the following steps: loading aminoguanidine salt onto activated carbon to prepare a deodorant; the deodorizing agent, the antibacterial agent and the dispersing agent are sequentially added into the viscose spinning stock solution, mixing and wet spinning are carried out, the deodorizing fiber is prepared, and the antibacterial agent is sodium alginate and / or carboxymethyl chitosan. The preparation process is simple, the cost is low, and the prepared deodorizing fiber and fabric are good in washing resistance and have long-acting antibacterial and deodorizing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional fibers, and in particular to a deodorizing fiber, a fabric, and a preparation process thereof. Background Art

[0002] With the development of society, the proportion of aging population is getting higher and higher. The aging substance palmitoleic acid (9-hexadecenoic acid) is easily accumulated in the sebum of the elderly. At the same time, palmitoleic acid is also produced after bacterial fermentation on the surface of human skin, which is oxidized and decomposed into 2-nonenal, emitting a smell similar to that of candles. At the same time, in order to improve the physical fitness, people pay more and more attention to exercise, and sweating after exercise will emit a sour smell. In addition, in social occasions, the smell of smoke adsorbed on clothes will also make people feel uncomfortable.

[0003] Based on this, the demand for textiles with deodorizing function is getting higher and higher. Nowadays, the research on textile deodorizing finishing technology has become mature, and the deodorizing effect of fabrics can be achieved by chemical or physical methods such as reduction, oxidation, neutralization, addition, condensation, and decomposition.

[0004] Among them, adding activated carbon to the fiber can significantly improve the fiber's deodorization performance, especially after modification, it has a large adsorption capacity and deodorization function for odors such as ammonia and hydrogen sulfide. However, the activated carbon deodorization technology has poor water washability.

[0005] In view of the above problems, existing research, such as the patent with publication number CN105887227B, discloses a method for preparing antibacterial and deodorizing viscose fibers. The method adopts a chemical reduction method to load nano silver ions on waste hair activated carbon particles, and then puts the particles into a viscose spinning stock solution to obtain a finished antibacterial and deodorizing viscose fiber by wet spinning. The waste hair activated carbon particles are formed by ball milling waste hair activated carbon, and the specific surface area is ≥700m 2 / g, the content of activated carbon in the finished antibacterial and deodorizing viscose fiber is 0.5-4.0%.

[0006] However, the above method uses silver ions at a high cost. Without adding metal ions, the deodorization method using other chemical antibacterial agents or natural plant antibacterial agents and activated carbon has a low elimination rate for 2-nonenal and a complicated preparation method. Summary of the invention

[0007] In view of the above-mentioned shortcomings of the prior art, the present invention provides a deodorizing fiber, a fabric and a preparation process thereof, so as to solve the problems existing in the prior art such as poor water washability of the activated carbon modified deodorizing fiber and low elimination rate of 2-nonenal.

[0008] To achieve the above and related purposes, the present invention adopts the following technical solutions:

[0009] The first aspect of the present invention provides a process for preparing a deodorizing fiber, comprising the following steps:

[0010] (1) pretreating biomass, mixing the pretreated biomass with an activating agent to prepare activated carbon;

[0011] (2) loading aminoguanidine salt onto activated carbon to prepare a deodorant;

[0012] (3) Adding a deodorant, an antibacterial agent, and a dispersant to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorant fiber, wherein the antibacterial agent is sodium alginate and / or carboxymethyl chitosan.

[0013] In one embodiment of the present application, step (1) further includes: mixing the pretreated biomass with an activating agent, activating, cooling, acid washing, water washing, filtering, and drying under an inert gas atmosphere to obtain activated carbon.

[0014] In one embodiment of the present application, in step (1), the specific surface area of ​​the activated carbon is 1000-2000m 2 / g.

[0015] In one embodiment of the present application, in step (1), the biomass is one or more of rice straw, wheat straw, and corn cob;

[0016] and / or, the activator is potassium carbonate and / or potassium hydroxide;

[0017] And / or, the mass ratio of biomass to activating agent is 1:(1-1.5).

[0018] In one embodiment of the present application, step (2) further includes: dissolving aminoguanidine salt in water, preparing an impregnation solution, and impregnating activated carbon in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 12-22%.

[0019] In one embodiment of the present application, in step (2), the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate, aminoguanidine carbonate or aminoguanidine hydrochloride.

[0020] In one embodiment of the present application, in step (3), the dispersant is one of sodium silicate, sodium aluminate, ammonium citrate, potassium tripolyphosphate, and potassium pyrophosphate;

[0021] And / or, the mass ratio of the deodorant, antibacterial agent, dispersant and viscose spinning solution is (2-5): (0.3-0.8): (0.05-0.1): (94.1-97.65).

[0022] The second aspect of the present invention provides a deodorizing fiber, which is prepared according to the above preparation process.

[0023] A third aspect of the present invention provides a deodorizing fabric, which is woven using the deodorizing fiber as a raw material.

[0024] In one embodiment of the present application, the fabric further includes cotton fiber, polyester fiber, silk fiber or wool fiber.

[0025] The beneficial technical effects of the present invention are:

[0026] Traditional activated carbon has low porosity and is easy to reach adsorption saturation in a short time. Therefore, the present invention first prepares biomass-based activated carbon. On the basis of reducing costs, the prepared activated carbon has the advantages of high porosity, large specific surface area and strong adsorption. The activated carbon is used as a porous carrier to load aminoguanidine salts that have a deodorizing effect on aldehyde gases such as 2-nonenal, which can further improve the elimination rate of the deodorant for odor molecules such as ammonia, acetic acid, and 2-nonenal, and will not easily reach adsorption saturation.

[0027] The aminoguanidine salt of the present invention can rapidly perform one-way chemical adsorption on aldehyde gases at room temperature, and undergo a dehydration reaction with the aldehyde gases, thereby achieving the purpose of deodorization, and the byproducts produced by the reaction, such as methyleneamine compounds, are easily volatile and then adsorbed by biomass-based activated carbon, and will not have a negative impact on the human body. In addition, in order to solve the problem of poor water resistance of deodorizing fibers, the prior art often adds cross-linking agents, such as silane coupling agents, carbamate cross-linking agents and other textile auxiliaries to improve the bonding strength between the deodorizing agent and the fiber, but this method is likely to have a negative impact on the softness and other properties of the fiber. And if the deodorizing fibers are to be given more functions, such as antibacterial properties, it is necessary to add additional antibacterial agents such as nano titanium dioxide, etc., which is costly and has a cumbersome preparation process.

[0028] The present invention directly selects sodium alginate and / or carboxymethyl chitosan as both antibacterial agent and binder. Sodium alginate has a broad spectrum of antibacterial activity and has a strong inhibitory effect on a variety of bacteria and fungi. Its antibacterial mechanism mainly includes the destruction of cell membranes and blocking the nutrient absorption of microorganisms. The antibacterial mechanism of carboxymethyl chitosan includes: 1. By adsorbing on the cell surface to form a layer of polymer film, the transport of nutrients into the cell is blocked or carboxymethyl chitosan is adsorbed on the cell membrane surface, which changes the permeability of the cell membrane, causing the loss of cytoplasm and separation of the cell wall, thereby playing an antibacterial and bactericidal role; 2. Carboxymethyl chitosan penetrates into the cell body and adsorbs the charged cytoplasm in the cell, causing flocculation, disrupting the normal physiological activities of the cell, or blocking the transcription of DNA in the bacteria, thereby inhibiting the reproduction of bacteria.

[0029] In the preparation process of the present invention, since the coagulation bath of wet spinning is a weak alkaline solution, the carboxyl group in the antibacterial agent can undergo an esterification reaction with the hydroxyl group in the coagulation bath, thereby presenting a gel state and having a spatial three-dimensional network structure. Under the action of the dispersant, the deodorant can be carried in this network structure, and the sodium alginate gel or carboxymethyl chitosan gel has high viscosity and can fix itself and the deodorant in the fiber matrix, so that the prepared deodorizing fiber has excellent water washability and lasting antibacterial and deodorizing properties, and will not have a negative impact on the softness of the fiber.

[0030] In addition, the present invention also controls the specific surface area, loading rate, and dosage of antibacterial agent and dispersant of activated carbon. On the one hand, it avoids self-agglomeration and adhesion of the deodorant and the antibacterial agent, thereby improving the uniformity of distribution; on the other hand, it avoids excessive concentration of the antibacterial agent, which may clog the spinneret, and excessively low concentration, which may result in poor antibacterial properties; and on the third hand, it ensures that the deodorant has a long-lasting deodorizing effect, thereby avoiding adsorption saturation in a short period of time.

[0031] The preparation process of the invention is simple, controllable, low-cost and has good industrialization prospect.

[0032] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION

[0033] Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as the general understanding of a person of ordinary skill in the art to which the present invention belongs. It should be understood that certain features of the present invention (described in the context of separate embodiments for clarity) may also be provided in combination in a single embodiment. On the contrary, multiple features of the present invention (described in the context of a single embodiment for brevity) may also be provided separately or in any suitable combination or in any other described embodiment of the present invention when appropriate. Certain features described in the context of various embodiments will not be considered as essential features of those embodiments unless the embodiment is inoperable without those elements. The present invention is further described below by specific specific examples, but it should be noted that the specific process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention, and the protection scope of the present invention cannot be limited thereto. All equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

[0034] The first aspect of the present invention provides a process for preparing a deodorizing fiber, comprising the following steps:

[0035] (1) selecting at least one of rice straw, wheat straw, and corn cob as biomass, washing the biomass with deionized water for multiple times, drying, crushing with a ball mill, and passing through a 100-150 mesh sieve to obtain pretreated biomass;

[0036] Potassium carbonate and / or potassium hydroxide are selected as activators, the pretreated biomass and the activator are mixed in a mass ratio of 1: (1-1.5), placed in a tube furnace, heated to 600-800° C. at a heating rate of 3-10° C. / min under an inert gas atmosphere, activated for 100-150 minutes, and cooled to room temperature at a cooling rate of 1-5° C. / min; wherein the inert gas is nitrogen and / or argon;

[0037] Use 0.1mol / L hydrochloric acid or 0.1mol / L sulfuric acid for pickling to remove metal impurities contained in the material, then wash repeatedly with deionized water, filter, and dry to obtain activated carbon.

[0038] In this step, the specific surface area of ​​activated carbon is 1000-2000m 2 / g.

[0039] (2) dissolving aminoguanidine salt in water to prepare an impregnation solution, and impregnating activated carbon in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 12 to 22%.

[0040] In this step, the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate, aminoguanidine carbonate or aminoguanidine hydrochloride;

[0041] In this step, parameters such as the concentration of the impregnation liquid, the impregnation ratio, the impregnation temperature, the number of impregnations, etc. are conventionally adjusted according to the load rate requirements and are not specifically limited here.

[0042] (3) Adding a deodorant, an antibacterial agent, and a dispersant to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorant fiber, wherein the antibacterial agent is sodium alginate and / or carboxymethyl chitosan.

[0043] In this step, the dispersant is one of sodium silicate, sodium aluminate, ammonium citrate, potassium tripolyphosphate, and potassium pyrophosphate;

[0044] In this step, the mass ratio of the deodorant, the antibacterial agent, the dispersant and the viscose spinning solution is (2-5): (0.3-0.8): (0.05-0.1): (94.1-97.65).

[0045] In this step, the wet spinning is a conventional wet spinning process, which will not be described in detail here.

[0046] The present invention also provides a deodorizing fiber, which is prepared according to the above preparation process.

[0047] The present invention also provides a deodorizing fabric, which is woven using the deodorizing fiber as a raw material.

[0048] Furthermore, the fabric includes cotton fiber, polyester fiber, silk fiber or wool fiber.

[0049] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0050] Example 1

[0051] (1) washing the corn cob with deionized water for multiple times, drying, crushing with a ball mill, and passing through a 100-mesh sieve to obtain a pretreated corn cob;

[0052] Potassium hydroxide was selected as an activator, and the pretreated corn cobs and potassium hydroxide were mixed in a mass ratio of 1:1, placed in a tube furnace, heated to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, activated for 150 minutes, and cooled to room temperature at a cooling rate of 3°C / min.

[0053] The material was pickled with 0.1 mol / L hydrochloric acid to remove metal impurities, then washed repeatedly with deionized water, filtered, and dried to obtain a specific surface area of ​​1800 m 2 / g activated carbon.

[0054] (2) Dissolving aminoguanidine hydrochloride in water to prepare an impregnation solution, and impregnating activated carbon in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 15%.

[0055] (3) Adding a deodorant, sodium alginate and sodium silicate to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorizing fiber, wherein:

[0056] The mass ratio of deodorant, sodium alginate, sodium silicate and viscose spinning solution is 3:0.5:0.05:96.45.

[0057] (4) Weaving the deodorizing fiber into deodorizing fabric.

[0058] Example 2

[0059] (1) washing the corn cob with deionized water for multiple times, drying, crushing with a ball mill, and passing through a 120-mesh sieve to obtain a pretreated corn cob;

[0060] Potassium hydroxide was selected as an activator, and the pretreated corn cobs and potassium hydroxide were mixed in a mass ratio of 1:1.2, placed in a tube furnace, heated to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, activated for 150 minutes, and cooled to room temperature at a cooling rate of 3°C / min.

[0061] The material was pickled with 0.1 mol / L hydrochloric acid to remove metal impurities, then washed repeatedly with deionized water, filtered, and dried to obtain a specific surface area of ​​1900 m 2 / g activated carbon.

[0062] (2) Dissolving aminoguanidine hydrochloride in water to prepare an impregnation solution, and impregnating activated carbon in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 18%.

[0063] (3) Adding a deodorant, sodium alginate and sodium silicate to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorizing fiber, wherein:

[0064] The mass ratio of deodorant, sodium alginate, sodium silicate and viscose spinning solution is 5:0.5:0.1:94.4.

[0065] (4) Weaving the deodorizing fiber into deodorizing fabric.

[0066] Example 3

[0067] (1) washing the wheat straw with deionized water for multiple times, drying, crushing with a ball mill, and passing through a 150-mesh sieve to obtain pretreated wheat straw;

[0068] Potassium hydroxide was selected as an activator, and the pretreated wheat straw and potassium hydroxide were mixed in a mass ratio of 1:1.5, placed in a tube furnace, heated to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, activated for 150 minutes, and cooled to room temperature at a cooling rate of 3°C / min.

[0069] The material was pickled with 0.1 mol / L hydrochloric acid to remove metal impurities, then washed repeatedly with deionized water, filtered, and dried to obtain a specific surface area of ​​1800 m 2 / g activated carbon.

[0070] (2) Aminoguanidine sulfate is dissolved in water to prepare an impregnation solution, and activated carbon is impregnated in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 20%.

[0071] (3) adding a deodorant, carboxymethyl chitosan and sodium silicate to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorizing fiber, wherein:

[0072] The mass ratio of deodorant, carboxymethyl chitosan, sodium silicate and viscose spinning solution is 5:0.8:0.1:94.1.

[0073] (4) Weaving the deodorizing fiber into deodorizing fabric.

[0074] Example 4

[0075] (1) washing the rice straw with deionized water for multiple times, drying, crushing with a ball mill, and passing through a 150-mesh sieve to obtain pretreated rice straw;

[0076] Potassium hydroxide was selected as an activator, and the pretreated rice straw and potassium hydroxide were mixed in a mass ratio of 1:1.5, placed in a tube furnace, heated to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, activated for 150 minutes, and cooled to room temperature at a cooling rate of 3°C / min.

[0077] The material was pickled with 0.1 mol / L hydrochloric acid to remove metal impurities, then washed repeatedly with deionized water, filtered, and dried to obtain a specific surface area of ​​1800 m 2 / g activated carbon.

[0078] (2) Aminoguanidine hydrochloride is dissolved in water to prepare an impregnation solution, and activated carbon is impregnated in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 22%.

[0079] (3) Adding a deodorant, sodium alginate and sodium silicate to a viscose spinning stock solution in sequence, mixing, and wet spinning to obtain a deodorizing fiber, wherein:

[0080] The mass ratio of deodorant, sodium alginate, sodium silicate and viscose spinning solution is 5:0.3:0.05:94.65.

[0081] (4) Weaving the deodorizing fiber into deodorizing fabric.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is:

[0084] The activated carbon is commercially available wood activated carbon with a specific surface area of ​​700m 2 / g.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is:

[0087] The activated carbon prepared in step (1) is used as a deodorant.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is:

[0090] The loading rate of activated carbon was 30%.

[0091] Comparative Example 4

[0092] The difference between this comparative example and Example 1 is:

[0093] Deodorant and sodium silicate are sequentially added into viscose spinning stock solution, mixed, and wet-spun to obtain deodorant fiber, wherein the mass ratio of the deodorant, sodium silicate and viscose spinning stock solution is 3:0.05:96.95.

[0094] Comparative Example 5

[0095] The difference between this comparative example and Example 1 is:

[0096] Deodorant, sodium alginate and sodium silicate are sequentially added to viscose spinning stock solution, mixed, and wet-spun to obtain deodorizing fiber, wherein:

[0097] The mass ratio of deodorant, sodium alginate, sodium silicate and viscose spinning solution is 5:3:0.05:91.95.

[0098] Performance Testing

[0099] Antibacterial property: According to GB / T 20944.3-2008 “Evaluation of antibacterial properties of textiles Part 3 Oscillation method”, the antibacterial properties of the fabrics before and after treatment against Staphylococcus aureus ATCC6538, Escherichia coli ATCC 25922 and Candida albicans ATCC10231 were determined by the oscillation flask method.

[0100] The deodorizing fabrics of Examples 1 to 4 and the fabrics of Comparative Examples 1 to 5 were tested for antibacterial properties, and the results were recorded as the initial antibacterial rate; then, the deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were washed according to the following method: at 25°C, the deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were soaked in a 20% sodium stearate solution for 5 minutes, then washed 5 times with clean water, dried, and a washing was completed. The deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were washed 10 times and 20 times, respectively. The antibacterial test results are shown in Tables 1 and 2.

[0101] Dissolution of antimicrobial substances: Test according to the dissolution test method of antimicrobial substances in Appendix A of GB / T 31713-2015. The specific test method is as follows:

[0102] Examples 1 to 4 were woven into deodorizing fabrics with specifications of 40s*40s / 144*85, and 1.5cm*1.5cm fabric samples were cut from different parts of the fabrics of each example as test samples, three pieces each;

[0103] Comparative Examples 1 to 5 were woven into fabrics with specifications of 40s*40s / 144*85, and 1.5cm*1.5cm fabric samples were cut from different parts of the comparative example fabrics as samples to be tested, three pieces each;

[0104] Three pieces of two-layer 100% polyester knitted fabrics sewn together were used as wash fabrics, the mass per unit area of ​​which was 125% of the mass per unit area of ​​the sample to be tested, and the size of each wash fabric was 30 cm*30 cm.

[0105] Wash the above-mentioned samples to be tested, the samples to be tested and the accompanying fabrics once according to the requirements of Appendix B and Appendix C of FZ / T 73023-2006 and set aside for use;

[0106] Prepare several standard blank samples according to Appendix A of FZ / T 73023-2006, cut them into 1.5cm*1.5cm, wash them once according to Appendix B of FZ / T 73023-2006, and set aside;

[0107] Sterilize the washed standard blank samples, the samples to be tested, and the samples to be tested at 103 kPa and 121° C. for 15 min for later use;

[0108] Staphylococcus aureus (ATCC 6538), Escherichia coli (ATCC 25922), and Candida albicans (ATCC10231) were selected as test strains, and multiple groups of antibacterial substance dissolution tests were performed on the above sterilized standard blank samples, each test sample, and each test sample. The antibacterial substance dissolution of each test sample and each test sample was determined based on the maximum inhibition zone width (D) of each test sample and each test sample against Staphylococcus aureus, Escherichia coli, and Candida albicans. The test results are shown in Table 3.

[0109] Deodorizing performance of textiles: The deodorizing performance of the deodorizing fabrics prepared in Examples 1 to 4 and the fabrics prepared in Comparative Examples 1 to 5 were tested in accordance with GB / T 33610.3-2019 "Determination of Deodorizing Performance of Textiles", as follows:

[0110] The reagents include: ammonia, acetic acid sample gas, isovaleric acid (purity 98.0%), 2-nonenal (purity 95.0%), diluent gas (nitrogen with a purity of 99.99% or above), and ethanol (analytical grade).

[0111] The size is (50±2.5)cm 2Four pieces of deodorizing fabrics of Examples 1 to 4 and four pieces of fabrics of Comparative Examples 1 to 4 were used as samples to be tested.

[0112] Gas chromatography: prepare several 500 mL glass conical flasks, half of which are used for sample testing and the other half for blank testing. Each example and comparative example is tested separately for isovaleric acid and 2-nonenal.

[0113] Before the test, the conical flask was purged with nitrogen gas with a volume greater than 5 times the volume of the conical flask, and the humidity and test environment were adjusted.

[0114] Accurately weigh 20 g of isovaleric acid in a volumetric flask and dilute to the mark with ethanol; accurately weigh 10 g of 2-nonenal in a volumetric flask and dilute to the mark with ethanol.

[0115] The above-mentioned samples to be tested are used for isovaleric acid and 2-nonenal testing respectively. Each sample to be tested is laid flat on the bottom of a conical flask, 1000mL of nitrogen is blown into the conical flask to exclude the air inside, and the bottle mouth is sealed with a sealing film. Use a syringe to take 5μL of the above-prepared isovaleric acid and 2-nonenal solutions, and inject them along the inner wall of the conical flask through the sealing film. The above solutions should not contact the samples to be tested. Seal the pinholes with a sealing film on the original sealing film.

[0116] Leave it to stand for 2 hours in the standard atmospheric environment specified in GB / T 6529.

[0117] Repeat the above steps for blank test without adding the sample to be tested.

[0118] After 2 hours of contact, hold the conical bottle mouth and shake the conical bottle containing or not containing the sample to be tested vigorously for about 20 times within 20 seconds. Insert the gas-tight injection needle vertically about 4 cm into the center of the sealing film at the conical bottle mouth. Use the gas-tight injection needle to extract the gas to be tested in the bottle, and determine the sampling amount of the gas to be tested according to the type of gas chromatograph used.

[0119] Detection tube method: Place each sample to be tested in a sampling bag, evacuate the gas in the sampling bag with an aspirator or vacuum pump, inject 3L of ammonia and acetic acid sample gas into the sampling bag with an air pump, let it stand for 2 hours, use a 100mL syringe to draw 100mL of the gas to be tested from the sampling bag containing the sample, and read the color change position scale through the detection tube.

[0120] The odor chemical component concentration reduction rate (ORR%) was calculated, and the calculation results are shown in Table 4.

[0121] Adsorption saturation: Using the deodorant fabric of Example 1, and the fabrics of Comparative Examples 1, 3, and 5 as test samples, each test sample was cut into a size of 25 cm × 25 cm, and placed in a test chamber filled with odor gas. At regular intervals, a gas detector was used to detect the change in the concentration of odor gas in the test chamber. When the concentration no longer changed, the test sample reached adsorption saturation, and the time when the concentration no longer changed was recorded. The test results are shown in Table 5.

[0122] The experimental data and analysis are as follows:

[0123] Table 1 Antibacterial test results of fabrics in each example and each comparative example 1

[0124]

[0125] Table 2 Antibacterial test results of fabrics in each example and each comparative example 2

[0126]

[0127]

[0128] (Note: The antibacterial rate against Staphylococcus aureus and Escherichia coli is ≥ 70%, and the antibacterial rate against Candida albicans is ≥ 60%, and the sample has antibacterial effect)

[0129] As can be seen from Table 1 and Table 2, after adding antibacterial agents to the viscose spinning dope, the wash resistance of the deodorant fabric is significantly improved, and it has long-term antibacterial performance. After 20 washes, the antibacterial rate drops between 4% and 7%. When no antibacterial agent is added, such as in Comparative Example 4, its antibacterial rate drops by about 25%, its wash resistance is poor, and it does not have antibacterial properties after multiple washes.

[0130] In addition, from the data of Examples 1 to 4 and Comparative Examples 1 to 2, it can be seen that the biomass-based activated carbon of the present invention has better antibacterial effect than conventional activated carbon and activated carbon with small specific surface area.

[0131] The antibacterial rate of the examples of the present invention is close to that of Comparative Examples 3 and 5, but the dosage in the examples is lower. Considering from the cost perspective, the parameters of the examples of the present invention are preferred.

[0132] Table 3 Test on the dissolution of antibacterial substances in fabrics of each example and Comparative Examples 1 to 3

[0133]

[0134]

[0135] (Note: The width of the antibacterial zone D: D ≤ 1 mm is non-dissolving, 1 mm < D ≤ 5 mm is slightly dissolving, 5 mm < D ≤ 10 mm is moderately dissolving, D > 10 mm is dissolving)

[0136] As shown in Table 3, after adding the antibacterial agent to the viscose spinning stock solution, the fixation fastness of the deodorant and the antibacterial agent on the fiber is good, the maximum inhibition zone width of the deodorizing fabric is less than 1.5 mm, and the dissolution of the antibacterial substance is non-dissolution and good micro-dissolution, which indicates that the deodorizing fabric after adding the antibacterial agent will not cause harm to human health and is safer and more reliable. The dissolution of the antibacterial substance in the fabric of Comparative Example 4 is moderate dissolution, and its safety is lower than the antibacterial deodorizing fabric of the present invention.

[0137] Table 4 Deodorization performance of fabrics in various embodiments and comparative examples

[0138] Test subjects Ammonia ORR / % Acetic acid ORR / % Isovaleric acid ORR / % 2-nonenal ORR / % Example 1 87.7 87.0 88.1 90.8 Example 2 90.7 91.4 91.8 92.9 Example 3 91.4 92.6 92.1 93.7 Example 4 91.6 91.5 93.6 93.0 Comparative Example 1 81.7 82.0 80.6 85.7 Comparative Example 2 83.3 85.1 84.9 75.0 Comparative Example 3 91.0 90.8 92.5 93.4 Comparative Example 4 82.2 81.6 80.1 83.6 Comparative Example 5 92.0 91.4 92.5 93.3

[0139] It can be seen from Table 4 that the combination of biomass-based activated carbon, aminoguanidine hydrochloride and antibacterial agent can improve the deodorizing performance of deodorizing fabrics, significantly increase the reduction rate of 2-nonenal, and has strong adsorption capacity for odor molecules.

[0140] The activated carbon in Comparative Example 1 has a small specific surface area and its adsorption capacity is inferior to the deodorizing fabric in the embodiment of the present invention.

[0141] The activated carbon in Comparative Example 2 has a small specific surface area and does not contain aminoguanidine salt, and has a poor adsorption effect on 2-nonenal and a poor deodorizing effect.

[0142] The sodium alginate and carboxymethyl chitosan selected in the present invention also have a certain deodorizing effect, and can work synergistically with activated carbon. Therefore, the comparative example 4 does not contain an antibacterial agent, and the deodorizing effect is not as good as the deodorizing fabric of the present invention.

[0143] Table 5 Adsorption saturation test of fabrics in embodiments and comparative examples

[0144] Test subjects Total time to reach adsorption saturation / h Example 1 56 Comparative Example 1 23 Comparative Example 3 30 Comparative Example 5 26

[0145] It can be seen from Table 5 that the deodorizing fabric prepared in the embodiment of the present invention has a long-lasting deodorizing effect, a long adsorption time, a high adsorption force, and is not easy to reach adsorption saturation.

[0146] However, the activated carbon in Comparative Example 1 has a small specific surface area and poor adsorption capacity, and is easily saturated with adsorption.

[0147] The loading rate of the activated carbon in Comparative Example 3 is high, which affects the porosity of the activated carbon to a certain extent, reduces its total adsorption capacity, and thus easily reaches adsorption saturation.

[0148] In Comparative Example 5, the sodium alginate content is too high. On the one hand, it is easy to clog the spinneret during the spinning process. On the other hand, it reduces the porosity of the activated carbon, affecting its adsorption capacity, and thus easily reaches adsorption saturation.

[0149] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a deodorizing fiber, characterized in that: The following steps are involved: (1) pretreating biomass, mixing the pretreated biomass with an activating agent to prepare activated carbon; (2) loading aminoguanidine salt onto the activated carbon to prepare a deodorant; (3) The deodorant, antibacterial agent and dispersant are sequentially added into the viscose spinning stock solution, mixed, and wet-spinned to obtain the deodorizing fiber, wherein the antibacterial agent is sodium alginate and / or carboxymethyl chitosan.

2. The preparation process according to claim 1, characterized in that: The step (1) further comprises: mixing the pretreated biomass with an activating agent, activating, cooling, acid washing, water washing, filtering and drying under an inert gas atmosphere to obtain the activated carbon.

3. The preparation process according to claim 1, characterized in that: In the step (1), the specific surface area of ​​the activated carbon is 1000 to 2000 m 2 / g.

4. The preparation process according to claim 1, characterized in that: In the step (1), the biomass is one or more of rice straw, wheat straw, and corn cob; and / or, the activator is potassium carbonate and / or potassium hydroxide; And / or, the mass ratio of the biomass to the activating agent is 1:(1-1.5).

5. The preparation process according to claim 1, characterized in that: The step (2) further comprises: dissolving the aminoguanidine salt in water to prepare an impregnation liquid, and impregnating the activated carbon in the impregnation liquid to obtain the deodorant, wherein the loading rate of the activated carbon is 12-22%.

6. The preparation process according to claim 1, characterized in that: In the step (2), the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate, aminoguanidine carbonate or aminoguanidine hydrochloride.

7. The preparation process according to claim 1, characterized in that: In the step (3), the dispersant is one of sodium silicate, sodium aluminate, ammonium citrate, potassium tripolyphosphate, and potassium pyrophosphate; And / or, the mass ratio of the deodorant, antibacterial agent, dispersant and viscose spinning solution is (2-5): (0.3-0.8): (0.05-0.1): (94.1-97.65).

8. A deodorizing fiber, characterized in that: The fiber is prepared according to the preparation process according to any one of claims 1 to 7.

9. A deodorizing fabric, characterized in that: The fabric is woven using the deodorizing fiber described in claim 8 as raw material.

10. The antibacterial and deodorizing fabric according to claim 9, characterized in that: The fabric also includes cotton fiber, polyester fiber, silk fiber or wool fiber.

Citation Information

Patent Citations

  • Preparation Method of Antibacterial and Deodorant Viscose Fiber

    CN105887227B

  • Deodorant

    CN101222944A

  • Bamboo charcoal, hemp stalk carbon and turf composite viscose

    CN103556259A

  • Preparation method and application of sodium alginate composite fiber containing nano activated carbon

    CN113969435A

  • Composite deodorizing viscose fiber, fabric and preparation method of composite deodorizing viscose fiber

    CN118727176A